Feasibility of XBRL in public sector reporting. - Choo, Zu Mou. (2008)
This study explores the feasibility of implementing XBRL for Singapore public sector reporting. The findings show that the XBRL is feasible for financial reporting purposes and would increase the level of transparency to the public. The increase is achieved through higher accessibility to the reported data.